Living Strategy Putting People at the Heart of Corporate Purpose - Gratton, Lynda (Pearson Business, 2000)
For corporate strategy to live and work, people have to understand strategy, and strategy makers have to understand people. They need a living strategy. "This insightful book has been the publishing event of the last few months - and rightly so. .... It's rounded off with a workbook - this makes an already reasonably priced book into even better value. If you want to tap into the current thinking and breathe life and purpose into people development, then make sure that you grab a copy." Training Magazine " People are our most important asset ", " We are a knowledge based company ", " All we have is our people ", are statements we increasingly hear, and statements which are all to often unsubstantiated by reality. For many people the actuality of organizational life is that they do not feel they are treated as the most important assets and they do not feel their knowledge is understood or used. The arguments for the central role of people can play in the creation of sustainable competitive advantage are compelling. Each of us has our own set of stories about how people have made a real difference to their business. Living Strategy demonstrates that the companies who will be most successful in the 21st century will be those that are capable of gathering and bonding talented, creative people, who are excited and motivated, who trust the company and are inspired by what they do. It places the behavior of individual employees at the center of wealth creation. This book shows executives how to design strategies that have meaning and purpose for people, without whose commitment they remain drawings on the wall chart. It will show line managers how to implement strategy and carry their people with them. It will bring strategy to life for businesses because it will bring strategy to life for people. Living Strategy puts forth three basic tenets that differentiate people from money and technology: we operate in time, we search for meaning, and we have soul. These tenets are then used as the basis for putting human capital at the center of corporate strategy. We operate in time Our current behavior is influenced by the memory of the past and by the beliefs of the future. Human development progresses through a shared sequence as skills and knowledge may take years to develop and attitudes and values area resistant to rapid change. We search for meaning We strive to interpret the clues and events around us, we actively engage with the world, to seek a se...
Online resource; Title from title page (viewed May 4, 2000)
Keywords: Human capital; Intellectual capital; Strategic planning; Corporate culture; Personnel management; Organizational Culture; Personnel Management; Capital intellectuel; Planification stratégique; Culture organisationnelle; Personnel; Direction